2020
DOI: 10.1002/lary.28949
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Influence of Electrode Array Length on Speech Recognition in Cochlear Implant Users

Abstract: Objectives/Hypothesis: Results from a prospective trial demonstrated better speech recognition for cochlear implant (CI) recipients implanted with a long lateral wall electrode array compared to subjects with a short array after 1 year of listening experience. As short array recipients may require an extended adaptation period, this study investigated whether differences in speech recognition continued through 4 years of CI use. Study Design: Long-term follow-up of a prospective randomized trial. Methods: Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 45 publications
3
33
1
Order By: Relevance
“…HRCT and magnetic resonance imaging had been conducted preoperatively and patients with cochlear anomalies and signs of sclerosis or obliteration were excluded from this study. We only included patients inserted with a Cochlear™ Contour Advance ® (CI24RECA, CI412/512/612) (= CA), Cochlear™ slim straight ® (422/522/622) (= SSA) or Cochlear™ slim modiolar ® (532/632) electrode array (= SMA) (Cochlear Limited, NSW, Sydney, Australia) and MED-EL Flex 24 , MED-EL Flex 28 and MED-EL Flex Soft (MED-EL, Innsbruck, Austria). Electrode arrays were inserted via cochleostomy (= CS), round window (= RW) and extended round window (= ERW) insertion.…”
Section: Study and Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…HRCT and magnetic resonance imaging had been conducted preoperatively and patients with cochlear anomalies and signs of sclerosis or obliteration were excluded from this study. We only included patients inserted with a Cochlear™ Contour Advance ® (CI24RECA, CI412/512/612) (= CA), Cochlear™ slim straight ® (422/522/622) (= SSA) or Cochlear™ slim modiolar ® (532/632) electrode array (= SMA) (Cochlear Limited, NSW, Sydney, Australia) and MED-EL Flex 24 , MED-EL Flex 28 and MED-EL Flex Soft (MED-EL, Innsbruck, Austria). Electrode arrays were inserted via cochleostomy (= CS), round window (= RW) and extended round window (= ERW) insertion.…”
Section: Study and Subjectmentioning
confidence: 99%
“…The patient chose the manufacturer following individual consulting. If the patient chose MED EL and showed residual hearing, the FLEX 24 was used in most cases. In patients implanted with a device from Cochlear™, the SSA or the SMA was used in patients with residual hearing, otherwise the CA was also used quite often due to the later availability of the SSA and the SMA.…”
Section: Study and Subjectmentioning
confidence: 99%
“…As the group around Canfarotta reported, patients with CI alone and longer electrodes seem to have a lower degree of frequency-to-place mismatch than patients with residual hearing and electric acoustic stimulation [24]. In addition, they found a better long-term speech recognition in patients with a 31.5 mm electrode, than those with a 24 mm array [46]. At the same time, the same research group observed a greater likelihood of preservation of the lower frequencies in patients with longer CDL (up to 36.5 mm) with the same electrode (31.5 mm) [47].…”
Section: Discussionmentioning
confidence: 89%
“…The insertion of the dummy insertion electrode to a length of 30 mm inside the SV convinced us to choose a 28 mm long electrode and flexible array. Also, for the reason that this patient was profoundly deaf across all frequencies tested preoperatively, electrical stimulation across the entire frequency range was thought to be necessary and as supported by recent reports [22][23][24].…”
Section: Discussionmentioning
confidence: 80%